Cold War on CNN, Part 2: Iron Curtain 1945-1947 (Jeremy Isaacs Productions, 1998)
Duration: 00:46:00 In the months following their victory in World War II, the alliance between the Soviet Union and the West quickly proves to be little more than a marriage of convenience. Suspicion clouds relations -- while a curtain descends over Europe.